Experimental analysis of a heat sink for electronic chipset cooling using a nano improved PCM (NIPCM). (2022) - Manoj Kumar, P.; Saminathan, Rajasekaran; Sumayli, A.; Mittal, Manoj; Abishek, A.S.; Atharsh Kumaar, A.S.; Reddy, Tadimarri Dinesh Kumar; Rinawa, Moti Lal
Abstract: The impacts of a phase changing substance (PCM) and a nano-improved phase changing substance (NIPCM) on the thermal performance of a heat sink to be used for an electronic chipset are investigated in this work. The paraffin with suitable melting temperature was utilized as the base PCM, and 1.0% weight fraction of nano-silica (SiO2 ) was used with paraffin while preparing NIPCM. A plate fin heat sink was established during the experimentation. The investigations were performed with three different configurations of heat sinks. The first configuration was the plain heat sink without amalgamation of any PCM, which was labeled as HS. It was further integrated into PCM and NIPCM based thermal dissipation systems, and named as PCM-HS and NIPCM-HS, respectively. The effects of varying power levels on three distinct heat sink modules (HS, PCM-HS, and NIPCM-HS) were explored in passive working modes. It has been discovered that the PCM may greatly boost the system's thermal performance, and that the NIPCM, when compared to the PCM, can further improvise the performance under passive cooling conditions. When compared to the PCM, the nano-PCM module can improve heat sink's thermal management through delaying heating time by up to 220%.